Beckett and Modernism (Palgrave Studies in Modern European Literature, 2018)
This book of collected essays approaches Beckett's work through the context of modernism, while situating it in the literary tradition at large. It builds on current debates aiming to redefine 'modernism' in connection to concepts such as 'late modernism' or 'postmodernism'. Instead of definitively re-categorizing Beckett under any of these labels, the essays use his diverse oeuvre - encompassing poetry, criticism, prose, theatre, radio and film - as a case study to investigate and reassess the concept of 'modernism after postmodernism' in all its complexity, covering a broad range of topics spanning Beckett's entire career. In addition to more thematic essays about art, history, politics, psychology and philosophy, the collection places his work in relation to that of other modernists such as T. S. Eliot, James Joyce, Wyndham Lewis, Gertrude Stein and Virginia Woolf, as well as to the literary canon in general. It represents an important contribution to both Beckett studies and modernism studies.